How school climate influences bullying behavior tendencies in junior high school - Ramadhani, Aisyah Putri; Utami, Adnani Budi; Ul Haque, Sayidah Aulia (Cendikia : Media Jurnal Ilmiah Pendidikan, 2025)
This study examines the design of an Islamic Religious Education (PAI) curriculum that promotes religious moderation in the digital era through a comprehensive literature review. The research aims to explore theoretical foundations, principles, and practical approaches for integrating religious moderation values into the PAI curriculum while addressing the challenges and opportunities presented by technological advancements. Using a qualitative approach, the study relies on primary and secondary literature, including academic books, journal articles, policy documents, and relevant educational research. Data were collected through systematic searches in academic databases using keywords such as "Islamic Religious Education curriculum," "religious moderation," "digital era," and "curriculum design." Content analysis was employed to identify key themes, including principles of religious moderation, curriculum development strategies, and the integration of digital tools in teaching and learning. The findings highlight the importance of embedding religious moderation values, such as tolerance, inclusivity, and respect for diversity, into the curriculum to foster harmonious interfaith relations. The study also emphasizes the critical role of digital technology in enhancing interactive and accessible learning experiences. Based on the analysis, a framework for designing a PAI curriculum that integrates religious moderation and digital competencies is proposed. This research contributes to the discourse on curriculum development by offering insights and practical recommendations for policymakers, educators, and curriculum designers. The proposed model seeks to prepare students to navigate the complexities of the digital era while upholding the principles of religious moderation